Impact of efavirenz, ritonavir-boosted lopinavir and nevirapine based antiretroviral regimens on the pharmacokinetics of lumefantrine and safety of artemether-lumefantrine in falciparum-negative HIV-infected Malawian adults stabilized on antiretroviral therapy - Banda, CG; Dzinjalamala, F; Mukaka, M; Mallewa, J; Maiden, V; Terlouw, DJ; Lalloo, DG; Khoo, SH; Mwapasa, V (American Society for Microbiology, 2018)
There is conflicting evidence of the impact of commonly used antiretroviral therapies (ARTs) on the pharmacokinetics of lumefantrine and safety profile of artemether-lumefantrine. We compared the area under the concentration-time curve (AUC0-14 days) of lumefantrine and safety profile of artemether-lumefantrine in malaria-negative human immunodeficiency virus (HIV) infected adults in two steps. In step 1, a half-dose adult course of artemether-lumefantrine was administered as a safety check in four groups (n=6/group): (i) antiretroviral-naïve, (ii) on nevirapine-based ART, (iii) on efavirenz-based ART and (iv) on ritonavir-boosted lopinavir-based ART. In step 2, a standard-dose adult course of artemether-lumefantrine was administered to a different cohort in three groups (n=10-15/group): (i) antiretroviral-naïve, (ii) on efavirenz-based ART and (iii) on ritonavir-boosted lopinavir-based ART. In step 1, lumefantrine's AUC0-14 days was 53% [95% CI: 0.27-0.82] lower in the efavirenz-based ART group than the ART-naïve group and was 2.4 [95% CI: 1.58-3.62] and 2.9 [95% CI: 1.75-4.72] times higher in the nevirapine and ritonavir-boosted lopinavir groups, respectively. In step 2, lumefantrine's AUC0-14 days was 1.9 [95% CI: 1.26-3.00] times higher in the ritonavir-boosted lopinavir group and not significantly different between the efavirenz- and ART-naïve groups (0.99 [95% CI: 0.63-1.57]). Frequent cases of haematological abnormalities (thrombocytopenia and neutropenia) were observed in the nevirapine group in step 1, leading to a recommendation from the data and safety monitoring board not to include a nevirapine group in step 2. Artemether-lumefantrine was well tolerated in the other groups. The therapeutic implications of these findings need to be evaluated among HIV-malaria co-infected adults.